Aesthetic Justice. Issue 1 (2nd January 2020) - Wisniowska, Magdalena
ABSTRACT: In his late essay "To Have Done With Judgment" Gilles Deleuze puts forward an alternative aesthetics to those based within the doctrine of judgment. He argues that to do justice to the work of art, one must recognise the creation of the new modes of existence in the work to come. This essay aims to deepen the understanding of Deleuze's concept of the "work to come" by going against the grain of contemporary scholarship's focus on the essay's ethical programme in order to explore its possible aesthetic, ontological and phenomenological interpretations. To do justice to the work to come is as much a question of the affective relationship with the work and what this relationship might mean ethically speaking, as it is of the ontological difficulty of establishing ground, or indeed, of the phenomenological problem of genetic constitution. Adopting a phenomenological perspective, the essay argues that to forsake judgment in favour of justice is to approach the artwork in terms of genesis, to appreciate existence within the field of experience as being in a continual process of development. Central to this approach is Deleuze's definition of combat as a productive interaction of forces, which results in new modes of existence being created.